Serum miR-146a and miR-150 as Potential New Biomarkers for Hip Fracture-Induced Acute Lung Injury - Li Gan; Tiansheng Sun; Bei Li; Jing Tian; Jianzheng Zhang; Xiaobin Chen; Jianfeng Zhong; Xiao Yang; Qi Li (Mediators of Inflammation)
Background. Acute lung injury (ALI) and subsequent pulmonary infection are the most severe and usually fatal complications for elderly hip fracture patients. It is necessary to find some biomarkers for early diagnosis and prognosis of it. Objective. This study is aimed at examining the differential expression of miR-146a, miR-150, and cytokines (IL-6 and IL-10) between younger and elderly rats suffering from hip fracture and investigating the possible meaning of them in early diagnosis and prognosis of ALI after hip fracture. Methods and Subjects. Elderly rats and younger rats were randomly divided into sham group and fracture group, respectively. Two fracture groups received hip fracture operations. The damage degree of ALI was evaluated by histological observation and pathological score. Cytokines were measured by ELISA; miR-146a and miR-150 were analysed by qRT-PCR. Results. After treatment, compared with the corresponding sham groups, the pulmonary histological score, the serum miR-146a concentrations, and the cytokine (IL-6 and IL-10) levels in serum and BALF were significantly higher (the miR-150 were lower) in the fracture groups (with the exception of IL-6 of the younger fracture group at 72 h, all P<0.05). Meanwhile, compared with the younger fracture group, the aforementioned variables were significantly higher (the miR-150 levels were lower) in the elderly fracture group (with the exception of serum IL-10 and pulmonary histological score at 8 h, all P<0.05). The results of linear regression analysis showed that serum miR-146a and miR-150 were significantly associated with pulmonary histological score. Conclusion. Hip fracture can result in significant systemic inflammation and ALI in the rats. Compared to the younger rats, the elderly rats suffered a more remarkable ALI after hip fracture. It may be related to the abnormal expression of miR-146a and miR-150. Serum miR-146a and miR-150 are potential biomarkers for diagnosis and prognosis of ALI after hip fracture.